Impact of the COVID-19 pandemic on university students’ psychological distress, well-being, and utilization of mental health services in the United States: populations at greatest risk - Russell, Elaine Cooper; Abidogun, Tolulope M.; Lindley, Lisa L.; Griffin, Kenneth W. (Frontiers in Public Health, 2024)
The COVID-19 pandemic led to major disruptions in the lives of university students. Using data from the National College Health Assessment surveys, both before the COVID-19 pandemic (pre-March 2020, n=88,986) and during the pandemic (Spring 2021, n=96,489), the present study examined mental health symptoms and utilization of mental health services among undergraduate students attending four-year universities in the United States. There were notable increases in measures of psychological distress and reductions in well-being from before the pandemic to during the pandemic. Losing a loved one from COVID, other COVID-related stressors, and loneliness were associated with higher rates of severe psychological distress, while well-being and resilience were associated with lower rates of severe psychological distress. Despite the significant increases in psychological distress observed during the pandemic, overall rates of mental health service utilization slightly decreased from pre-pandemic to during the pandemic. COVID-related stressors and loneliness were associated with higher rates of mental health services utilization, while well-being and resilience were associated with lower rates of mental health services utilization. Analyses revealed that several demographic groups were at an elevated risk for severe psychological distress, including non-binary, female, and sexual minority students, and especially those who identify as both non-binary and non-heterosexual. Predictors of severe psychological distress included those who experienced loneliness, COVID-19 related stressors, and loss of a loved one from COVID-19. Results indicated that students of color, especially female students of color, were at an elevated risk